KNOWLEDGE SHARING BEHAVIOUR INFLUENCES: A CASE OF LIBRARY AND INFORMATION SCIENCE FACULTIES IN IRAN - Fahimeh, Babalhavaeji; Kermani, Zahra Jafarzadeh (Malaysian Journal of Library and Information Science, 2011)
The dynamism of a new economy requires information professionals to not only quickly create knowledge but also to acquire and apply knowledge through knowledge sharing. As such, determining factors that may influence knowledge sharing behaviour constitutes an important area of research. This paper aims to determine the factors that influence knowledge sharing amongst Library and Information Science (LIS) faculties, which in this context refers to attitude, intention and intrinsic motivation. Also, the paper identifies the effect of two demographic variables (type of institute and length of teaching experience) on knowledge sharing behaviour. Data were collected through survey questionnaire returned by 93 full-time LIS teaching staff in governmental and private universities (Islamic Azad universities) in Iran. Results showed that among demographic variables a significant difference was found between knowledge sharing behaviour of LIS educators with different teaching experiences (.027) but observed no significant difference between knowledge sharing behaviour of LIS faculties working in governmental universities and those working in Islamic Azad universities. The researchers also found a significant relationship (0.000) between attitude of educators toward knowledge sharing and their intention to share knowledge. Results showed that intention and intrinsic motivation influence knowledge sharing behaviour of the LIS educators sampled.